Analysis of Students' Reading Skills in Indonesian Language Learning at Elementary School - Maknun, Lu'luul; Agus Darmuki; Irfai Fathurrohman (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the reading skills of elementary school students in Indonesian language learning. The research employs a qualitative method using a literature review approach by analyzing ten accredited journal articles focusing on reading difficulties among elementary students. Data were collected through documentation techniques and critically analyzed to identify patterns of reading challenges and effective strategies to address them. The findings show that students in lower grades predominantly face technical difficulties such as recognizing letters, reading syllables, and reading fluency, while students in higher grades encounter more complex problems related to reading comprehension and correct pronunciation. Internal factors such as memory weakness, low motivation, and lack of concentration, along with external factors like limited literacy facilities and conventional teaching approaches, contribute significantly to students' reading difficulties. Persistent problems in reading are found to negatively affect students' academic achievements and psychological well-being. Therefore, early detection of reading difficulties, the application of adaptive and varied teaching strategies, and strong collaboration among teachers, schools, and parents are essential steps to enhance students' literacy skills and ensure academic success. This study highlights the urgent need for integrated efforts in improving reading abilities from the early stages of elementary education. Keywords : reading skills, Indonesian language learning, elementary school, literacy